Інтеграція штучного інтелекту та інтернету речей: розвиток розумних міст через адаптивний штучний інтелект - Милютін, О. Є. (ХНУРЕ, 2024)
The Internet of Things (IoT) technology has gained considerable popularity in various industries and is actively used in combination with intelligent systems. The integration of artificial intelligence (AI) technologies with IoT extends their functionality. This thesis discusses the evolution from neural networks to cognitive modelling, emphasising the shift from traditional methods to more flexible and adaptive approaches to create efficient IoT systems that can adapt to a changing environment, opening up new perspectives for optimising device performance and expanding capabilities in the field of cognitive computing
Keywords: штучний інтелект; модель Коттера; Eight Disciplines; AI; Lean Change Management